Aktivitas Fisik dan Pola Makan dengan Kadar Gula Darah pada Pasien Diabetes Melitus - Afriani Fatur Reski; Safruddin; Nur Ilah Padhila; Andi Yuliana (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Diabetes Mellitus is a disease that occurs due to excessive blood sugar levels (hyperglycemia) in response to the inability of the pancreas to produce insulin. This study aims to determine the relationship between physical activity and diet with blood sugar levels in diabetes mellitus patients at UPT Puskesmas Tana Lili. The research design used was an analytic descriptive design with a cross sectional approach using a total sampling technique with a sample of 43 respondents. The relationship test was carried out using the chi square test with a significance level of α<0.05. The results showed that there was no relationship between physical activity and diet with blood sugar levels in diabetes mellitus patients at the UPT Puskesmas Tana Lili. This research can be an input for health workers to provide education about the importance of doing regular physical activity and maintaining a healthy diet, so as to increase physical activity and a good diet for people with diabetes mellitus.